PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAMUR TIRAM PUTIH (Pleurotus florida) - Murdaningsih Murdaningsih; Modesta Lue (Agriculture Faculty of Flores University, 2014)
This study aims at revealing the impact of plant media on the growth and yield of white oyster mushroom (Pleurotusflorida) and finding out what plant media that can give the optimal growth and yield. The design uses in this study was random block design with the treatment of Mbayam (Bayam wood powder), Mmeranti (Meranti wood powder), Mkemiri (Hazelnut wood powder), Mjerami (straw). The observation variables used in this study were the prime emergence of the fruit, the number of fruit clumps, number of fruits per clump, harvesting age, the diameter of fruit, the length of fruit stalk, harvesting interval, the weight of the fruit, and REB value. The result of the study indicated that straw planting media was not able to grow mushroom and was contaminated. Planting media of bayam wood powder with Meranti wood powder, Bayam wood powder with hazelnut wood powder, and Bayam wood powder with straw makes a difference respectively, as follows: the primary emergence of fruit was 54:58 HST, 54:57 HST, and 54:0 HST, the number of fruit clumps were18,1%, 28,8%, and 100%, the number of fruit per clump were 4,0%, 13,9%, and 100%, and harvesting age were 4,1:4,9, 4,1:4,1, and 4,1:0. Planting media of Bayam wood powder provided the high average in the primary emergence of the fruit of 54 HST, 118.7 of fruit clumps, 15.1 of fruit/clump,6cm of fruit diameter, 2.9cm length of fruit stalk, 6.6 days of harvesting interval, 68.9gram of fruit weight and 0.68 of REB value.